2004
DOI: 10.1128/jvi.78.20.11051-11060.2004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Expressed Genes in Scrapie-Infected Mouse Brains by Using Global Gene Expression Technology

Abstract: The pathogenesis of prion diseases, a class of transmissible fatal neurodegenerative diseases in humans and animals, is still unclear. The aim of this study was to identify the differentially regulated genes that correlate with the development of prion diseases for a better understanding of their pathological mechanisms. We employed Affymetrix Mouse Expression Arrays 430A containing >22,000 transcripts and compared the global gene expression profiles from brains of mice who were intracerebrally inoculated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
157
2
13

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(184 citation statements)
references
References 59 publications
12
157
2
13
Order By: Relevance
“…We thus conclude that PrP sc may affect Dab1 phosphorylation and A production. PrP sc inoculation gives rise to a wide range of molecular responses in infected brains (Xiang et al, 2004) including in oxidative stress (Choi et al, 1998;Martin et al, 2007;Yun et al, 2006), which is also described in sCJD patients (Freixes et al, 2006;Pamplona et al, 2008;Petersen et al, 2005). Indeed, sCJD patients with PrP sc type 1 and MM polymorphism at codon 129 are characterized by faster evolution and decreased life expectancy compared with PrP sc type 2 with other polymorphisms at codon 129 (Uro-Coste et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We thus conclude that PrP sc may affect Dab1 phosphorylation and A production. PrP sc inoculation gives rise to a wide range of molecular responses in infected brains (Xiang et al, 2004) including in oxidative stress (Choi et al, 1998;Martin et al, 2007;Yun et al, 2006), which is also described in sCJD patients (Freixes et al, 2006;Pamplona et al, 2008;Petersen et al, 2005). Indeed, sCJD patients with PrP sc type 1 and MM polymorphism at codon 129 are characterized by faster evolution and decreased life expectancy compared with PrP sc type 2 with other polymorphisms at codon 129 (Uro-Coste et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Genes for several cathepsins and S100 protein were also evident [126]. The authors reported that elevated gene levels correlated temporarily with the onset of PrP Sc accumulation and the activation of glia, which may have contributed to neuronal cell death [126]. The above studies demonstrate the potential of genes as diagnostic markers of prion disease.…”
Section: Transcriptional Markersmentioning
confidence: 96%
“…More recently, using microarray technology Xiang et al [126] identified 121 genes from brains of scrapie-infected mice whose expression was at least twice that in control animals. The genes expressed were found to encode proteins involved in several functions including proteolysis, protease inhibition, cell growth and maintenance, immune response and molecular metabolism.…”
Section: Transcriptional Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…The first application of DNA microarrays to human neurologic disease revealed gene expression abnormalities in a transgenic mouse model of Huntington's disease (HD) (15). Subsequently, gene expression abnormalities have been found in a number of neurodegenerative diseases, including AD (1), ALS (5), PD (9,10,16), prion diseases (25), frontotemporal dementia and PSP (10), and multiple sclerosis (22), suggesting that impacting the genome is another common feature of these disorders. These studies of human neurodegenerative disease reveal some general principles.…”
mentioning
confidence: 99%